"What Appeals to the Students from My Odds and Ends of Knowledge". Issue 1 (May 2015) - Martus, Steffen
Abstract Jacob and Wilhelm Grimm saw science and the humanities as practised in research and teaching as a way of life which could also be highly political. As a result, in 1837 the brothers and five other professors joined together in protest as the "Göttingen Seven", risking dismissal from their positions and banishment.